Tariff, Wages and Compensation: A General Oligopolistic Equilibrium Analysis - Aaheli Ahmed; Sugata Marjit; Debashis Chakraborty (CESifo GmbH, 2025)
A major section of the existing literature on strategic trade policy, following a partial equilibrium framework, observed that imposition of tariff by the domestic country leads to a rise in their wage level. Analysis on the impact of strategic trade policy intervention (tariff) on wages and welfare in a two-country general oligopolistic equilibrium (GOLE) model framework in the current paper leads to a number of interesting results. First, imposition of tariff does not affect the wages in domestic country. In addition, the welfare of the tariff-imposing country unambiguously comes down. Second, a comparison of the revenue generated from tariff and the subsidy required to compensate the affected workers reveals that when only trade in final goods is allowed, such compensation is possible beyond a specific level of tariff rate, which is directly related to foreign tariff rate. In effect, a high value of foreign tariff implies a lower ability of the domestic government to subsidize the workers. Third, however, when trade in both final and intermediate goods take place, the opposite results emerge, where tariff revenue can compensate the workers up to a certain level of tariff rate. The underlying logic is that imposition of tariff may lead to a fall in the overall demand for workers in the domestic country. The results are of crucial policy relevance, especially given the increasing participation of developing countries in Global Value Chains (GVCs) and re-emergence of tariff protectionism in several countries.
Keywords: D43; J33; L13; I31; 330; Cournot Competition; tariff; wage; compensation; general oligopolistic equilibrium (GOLE); welfare